Socio-professional Antecedents of Conciliation between Work and Family Role among Tunisian Physical Education Teachers - Zemmel, Hedi; Baaziz, Mohamed; Saii, Badai; Jannet, Zouheir Ben (Advances in Social Sciences Research Journal, 2024)
Background: Balancing work and family are an important issue these days, as demands and commitments in both contexts have increased. Aims: The aim of this study was to study the issue of family-work balance among Tunisian physical education teachers, and to identify the differences between men and women as well as the main factors influencing the relationship family-work. Method: 486 physical education teachers (342 men, mean age = 42.35 ±5.554, and 144 women, mean age = 42.80 ±7.708) belonging to three Tunisian governorates participated voluntarily to our study. Results: The results obtained from the MANOVA analysis showed the impact of gender and family status on reconciliation (Gender: [Lambda of Wilks = ,978 < 1, D = 3,551, p = 0,014 < p = 0,05]; Marital status: [Lambda de Wilks = ,906 < 1, d = 8,134, p = 0,000 < p = 0,05]), but work place had no effect: [Wilks' Lambda = .990 < 1, D = .830, p = 0.546 > p = 0.05]. Conclusion: Our statement therefore underlines the fact that the work-family conflict is very present among PE teachers in the south-western of Tunisia, contrary to the image perceived by society which provides that teachers have a working time that allows them to live comfortably.